Time and Processes in the Church: The «Reasonable Duration» of Canonical Processes as a Fundamental Right of the Faithful - Morán Bustos, Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
The present article defends the incorporation of the «right to a reasonable duration» of the processes to complete the right to effective legal tutelage recognized in can. 221. Taking as a starting point the idea that the procedural speed is not an essential principle of the proceedings, but a pastoral principle, characteristic of a community like the Church, which is concerned with the stormy process of annulment proceedings. Although the fundamental reason for the process is the search for the truth of the bond, so that the procedural speed is of a subsidiary and documental nature, also swiftness must be sought as a requirement of a fundamental right. With the true causes for the delay in the processes pointed out, the author proposes to «canonize» the right to a process without unjustified delays typical of the majority of «secular» codes, and to do it through what could be called «the right (fundamental) to a reasonable duration of processes». This fundamental right would come to be a principle of developmental action of the entire process, and would become a reality in behavioural guidelines on the part of all legal operators; this way it would be possible to go beyond mere recommendations, enabling the establishment of concrete guidelines of action, even corrective mechanisms for the lack of diligence.